The Discomfort of Dialectics. Gramsci, the National-Popular, and Workerist Critique - Desogus, Paolo (International Gramsci Journal, 2025)
This essay examines the Gramscian concept of the national-popular, highlighting its central role within the philosophy of praxis as both a cultural and political category. Far from being a merely literary notion, the national-popular is shown to be integral to the formation of a revolutionary subject and to the dialectical overcoming of the historical divide between people and nation, a separation reinforced by post-unification bourgeois hegemony in Italy. Through a critical engagement with the theoretical trajectories of Italian workerism and post-workerism—especially the writings of Mario Tronti and Toni Negri—the essay contrasts the Gramscian emphasis on mediation, hegemony, and cultural struggle with a vision of antagonism rooted in immediacy and spontaneity. These post-Hegelian and anti-dialectical positions, it is argued, ultimately reflect key features of neoliberal ideology, despite their claims to radicalism. By returning to Gramsci’s elaboration of the national-popular as a process of cultural elevation and political unification, the essay proposes a framework for understanding class struggle that avoids both economist and mythic conceptions of resistance. The national-popular thus emerges as a concept capable of informing contemporary emancipatory politics, grounded in the dialectical production of collective will and oriented toward the construction of a new communist civilization.